Pemanfaatan Lokal Wisdom dalam Membangun Desa Tematik dan Meningkatkan UMKM - Chairul Fajar Tafrilyanto; Septi Dariyatul Aini; Sri Indriati Hasanah; Moh. Zayyadi; Rofiva Rofiva; Bambang Kurnadi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
This community service activity explores the synergy between the concept of "Village Tematik," the enhancement of Micro, Small, and Medium Enterprises (UMKM), and the utilization of Local Wisdom. Village Tematik represents a village development approach that emphasizes the unique identity and strengths of a region. In this context, Local Wisdom serves as a valuable asset that can create attraction and added value for local UMKM products and services. Through this activity, we try to empower the community empowerment in uncovering and harnessing Local Wisdom can yield innovative and distinctive local products, capturing the interest of markets. Furthermore, it outlines practical steps inestablishing Village Tematik, engaging the community, and elevating the economic well-being of individuals through UMKM. This approach aims to foster the sustainable growth of villages, generate local employment opportunities, and preserve the distinctiveness of Local Wisdom. The insights provided herein are valuable for policymakers, development practitioners, and all stakeholders interested in supporting theevolution of Village Tematik and Local Wisdom-based UMKM development.